2017
DOI: 10.1002/2017tc004673
|View full text |Cite
|
Sign up to set email alerts
|

Imprint of Rupture Directivity From Ground Motions of the 24 August 2016 Mw6.2 Central Italy Earthquake

Abstract: An Mw6.2 earthquake occurred in Central Italy on 24 August 2016. The objective of this study was to reveal the imprint of rupture directivity using the strong motion recordings. The strong motion stations were separated into two groups: southeast (SE) and northwest (NW). The effects of rupture directivity on the peak ground acceleration (PGA), peak ground velocity (PGV), and pseudo spectral acceleration (PSA) were investigated. The observed values of these parameters were compared with predicted values derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The two largest mainshocks, the 24 August Mw = 6.1 Amatrice and the 30 October Mw = 6.5 Norcia, ruptured adjacent normal faults with ancillary structures (Cheloni et al, , Livio et al, ) and with overlapping slip on shallow faults surfacing on the western slope of the Vettore mountain range (Galli et al, ; Pucci et al, ). While some authors have modeled the 24 August shock, as continuous slip on a single fault (Huang et al, ), others proposed bilateral rupture with hypocenter located in between two separate faults (Liu et al, ; Ren et al, ; Tinti et al, ). The relatively young normal faults accommodate the 2–3 mm/year of extension across the mountain range.…”
Section: Introductionmentioning
confidence: 99%
“…The two largest mainshocks, the 24 August Mw = 6.1 Amatrice and the 30 October Mw = 6.5 Norcia, ruptured adjacent normal faults with ancillary structures (Cheloni et al, , Livio et al, ) and with overlapping slip on shallow faults surfacing on the western slope of the Vettore mountain range (Galli et al, ; Pucci et al, ). While some authors have modeled the 24 August shock, as continuous slip on a single fault (Huang et al, ), others proposed bilateral rupture with hypocenter located in between two separate faults (Liu et al, ; Ren et al, ; Tinti et al, ). The relatively young normal faults accommodate the 2–3 mm/year of extension across the mountain range.…”
Section: Introductionmentioning
confidence: 99%
“…C d γ indicate greater significance of the azimuthal variation of the residuals. As shown in Figure a, the v r / β values generally show a pronounced trend of decrease with increasing γ , indicating the vital impact of γ on the retrieved v r / β parameters, which has been widely verified (Pacor, Gallovič, et al, ; Ren, Wang, & Wen, ). In addition, larger v r / β values appear to result in the larger values of Max.…”
Section: Source Rupture Directivitymentioning
confidence: 54%
“…The kinematic source models for the M L 6.0 mainshock and two subsequent major earthquakes ( M L 5.9 and 6.1) were inverted using near‐source strong‐motion data, teleseismic waveforms, and geodetic data to reveal the slip heterogeneity, rupture directivity, and seismogenic mechanism (Chiaraluce et al, ; Liu et al, ; Pizzi et al, ; Scognamiglio et al, ; Tinti et al, ). According to analyses of the spatial distributions of various ground‐motion intensity measures, Ren et al () both confirmed the asymmetrical bilateral rupture propagation of the M L 6.0 mainshock and explained the directivity effects, especially on short‐period ground motions. Similarly, Convertito et al () inferred the horizontal source rupture directivity of the M L 6.0 mainshock by analyzing the peak ground velocity, and they suggested a contribution from the dynamic strain, enhanced by rupture directivity, to the occurrence of the ongoing aftershocks.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations